Point-of-care ultrasound as a competency for general internists: a survey of internal medicine training programs in Canada - Ailon, Jonathan; Nadjafi, Maral; Mourad, Ophyr; Cavalcanti, Rodrigo (Canadian Medical Education Journal, 2016)
Background: Point-of-care ultrasound (POCUS) is increasingly used on General Internal Medicine (GIM) inpatient services, creating a need for defined competencies and formalized training. We evaluated the extent of training in POCUS and the clinical use of POCUS among Canadian GIM residency programs. Method: Internal Medicine trainees and GIM Faculty at the University of Toronto were surveyed on their clinical use of POCUS and the extent of their training. We separately surveyed Canadian IM Program Directors and Division Directors on the extent of POCUS training in their programs, barriers in the implementation of POCUS curricula, and recommendations for POCUS competencies in IM. Results: A majority of IM trainees (90/118, 76%) and GIM Faculty (15/29, 52%) used POCUS clinically. However, the vast majority of resident (111/117, 95%) and GIM Faculty (18/28, 64%) had received limited training. Of the Program Leaders surveyed, half (9/17, 53%) reported POCUS clinical use by their trainees; however only one quarter (4/16, 25%) reported offering formal curricula. Most respondents agreed that POCUS training should be incorporated into IM residency curricula, specifically for procedural guidance. Conclusions: A considerable discrepancy exists between the clinical use of POCUS and the extent of formal training among Canadian IM residents and GIM Faculty. We propose that formalized POCUS training should be incorporated into IM residency programs, GIM fellowships, and Faculty development sessions, and identify POCUS skills that could be incorporated into future IM curricula.